The “Upright Confession” of the Empress Catherine II - Łucewicz, Ludmiła (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2018)
The author of the article focuses attention on the “Upright Confession” (1774), written by the Russian Empress Catherine II in the form of a letter to her new favourite Grigory Potemkin. Catherine speaks to her lover openly about her liaisons with other men. She tries to explain her amorousness in terms of “natural” properties of her “nature”, an Enlightenment concept current at the time. While in fact admitting to adultery, the Empress never mentions sin as such. There is no remorse, no repentance in Catherine’s “Upright Confession”. What is foregrounded is the frankness of the account, slightly coloured by irony. Thus, in her letter of confession the Russian Empress as though places herself beyond the traditional morality.